Environmental education in the reconstruction of bordering river Ribeirão da Penha and increase in the urban trees the city of Itapira – SP - Martelli, Anderson; Cardoso, Mariana de Moraes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Nowadays, a concern for the environment is present in the lives of most of the population. This article discusses the importance of bordering river, degraded areas by human action and recovery of ciliary vegetation found in urban areas through environmental education program developed by the Department of Agriculture and Environment Itapira. This strip of vegetation carry out action the barrier function and protection of water sources and water courses, server as ecological passageway, linking forest fragments allowing the transit of animals, taking them out of isolation. Bordering river are secured by law, but, there are still areas that have been deforested and degraded others who continue without recomposition plant. Although the importance the topic is rarely discussed and studied, especially in academic. This article portrays the reconstruction of bordering river on the riverside of Ribeirão da Penha, the main water course that cuts through the city limits of the Itapira-SP City and where water comes from the provide tanks, with the planting of 150 trees by students in the 8th year Ativa school emphasizing environmental education.